THE EFFECTIVENESS OF GROUP GUIDANCE SERVICES WITH FISHBOWL METHOD TO IMPROVE FURTHER STUDY DECISION MAKING FOR VOCATIONAL SCHOOL COUNSELOR - Ibnu Athiyah (IJIET (International Journal of Indonesian Education and Teaching), 2020)
This study aimed to examine the effectiveness of group counseling services using the fishbowl method to improve decision making for further study in vocational school counselor. This research was an experiment study with one group pretest- posttets design. The subject of vocational counseling guidance teachers (school counselors) research in East Jakarta. The population in this study were 32 vocational school counselors. The sampling technique used was purposive sampling of 15 people. The research instrument used was the scale of the decision made by the researchers themselves, with a validity of 0.304 (Pearson Product Moment) and reliability of 0.894 (Alpha Cronbach), data normality test with the Shapiro-Wilk test (0.567 0.05). Data analysis techniques using parametric statistics with paired sample t-test with (t = -18.263, p 0.05). The results of the study provide an understanding that group guidance services with the fishbowl method were effective in increasing further study decision making in vocational school counselors.